Processos de formação continuada de educadores para os anos iniciais na área de ciências da natureza: um panorama investigativo-reflexivo - Bender, Darlize Déglan Borges Beulck (2023)
In Science Education, the teacher education theme has been a prominent topic in academic research for years, as the quality development of this process, whether initial or continuous, is directly related to the teaching and learning process of students. The learning of Natural Sciences (NS) is highlighted in the literature to occur from the early years of schooling, in order to contribute to the formation of conscious and active citizens in today's society. However, there are gaps in the research regarding the investigations focused on the continuous education (CE) of teachers for teaching NS in the Elementary School's Early Years (ESEY), especially regarding the strategies employed in these processes that could generate an understanding of their mechanisms of operation. Therefore, this study aims to investigate the historical productions on the CE processes of ESEY teachers in relation to the teaching of NS, in order to establish an overview that can contribute to the understanding and qualification of these processes by trainers, researchers, teachers, and students interested in the subject. To achieve this, seven literature review works were carried out, two based on publications from the National Meeting of Research in Science Education, two based on national and international scientific articles, and three based on national theses and dissertations, which presented reports on the development of CE courses with ESEY teachers on NS. After initial analyses, to understand the formative processes, they were divided into three periods: pre-formative, formative, and post-formative. In the pre-formative period, an overview of the stages preceding the CE courses was gathered, and some deficiencies in the initial training of teachers in NS were observed, as well as the priority given to literacy in the native language and other subjects. It also became evident that the choice of CE topics is made by researchers, which goes against the recommendations of theorists in the field regarding the importance of teachers' protagonism in their own training. In the formative period, moments of collective and individual reflection, reorganization of teaching activities, concept formation, and development of scientific vocabulary by participating teachers were highlighted. Through the trainers' reports on CE, eight guiding principles were identified, which can assist future trainers and researchers in planning and implementing formative courses. In the post-formative period, the positive legacy of CE for teachers and the school community was noticed; however, there was a lack of long-term follow-up by researchers to continue supporting teachers and capturing long-term results of the offered training. Theorists in the field emphasize the importance of listening to, supporting, and advising teachers after training to achieve effective formative changes. Therefore, it can be concluded that establishing a comprehensive overview of the continuous formative processes focused on the teaching of NS in ESEY, considering practical development and theoretical foundations, leads to a better understanding of their gaps and potentialities, assisting future trainers and researchers in the qualification of future actions, as well as indicating perspectives for more integrated policies needed in the field.